Granulomatous Pancreatitis in a Patient with Acute Manifested Insulin-Dependent Diabetes Mellitus - Václav Mandys; Michal Kheck; Michal Anděl (Hindawi Limited, 2014)
Isolated granulomatous noncaseating pancreatitis is a rare condition exceptionally described in human population. We demonstrate a case of the a 71-years-old female patient suffering from recent diabetes mellitus, generalized atherosclerosis and hypertension who died due to pulmonary embolism and terminal bronchopneumonia. Lipomatosis of pancreatic tissue was observed during the postmortem examination. Histological examination of pancreatic tissue discovered multiple small noncaseating epithelioid cell and giant cell granulomas, partly replacing the islets of Langerhans. To our knowledge, our case represents the first description of noninfectious granulomatous pancreatitis associated with acute manifested insulin-dependent diabetes mellitus.